The protection of train crews during their work in the agglomeration of Budapest - Erdei, Attila (Studia Mundi – Economica, 2021)
A peaceful, prosperous era for Hungary began with the Compromise of 1867. Especially the development of Budapest was impressive at the turn of the 19th and 20th centuries, which made the capital a real metropolis in the heart of the Carpathian-Basin. At this time, the establishment of the proper railway network and railway connections gave the basis of the economic prosperity of the country. Development of railway had not only positive, but also negative effects, such as the emergence of dangerous criminals, robbers, thieves, violent people who harmed the passengers and threatened the safety of rail transport. In the recent years, the number of violence attacks increased against the train-crew members (e. g. ticket inspectors, train drivers). Especially trains running in the agglomeration of Budapest have required police actions. The study consists of three main parts. The first part contains a brief presentation of the Hungarian railway system, the second part presents the suburban and local railways (HÉV) in the agglomeration of Budapest, and the third part presents the nature and number of crimes committed against the train crew members and the security regulations against attacks.
Keywords: train; abuse; law; transportation; railway